(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
In this article the results of hydrodynamic studies of albumin aqueous solutions at the presence of cis-dimethylsulphoxide complex of platinum (II) are presented. By the viscosytmetric and densitometric methods behaviour of these systems is studied at 20–50℃ temperature range. For the explanation of obtained results the model of compact spheroid is used.